2021
DOI: 10.1111/hequ.12346
|View full text |Cite
|
Sign up to set email alerts
|

Academic freedom in contemporary Britain: A cause for concern?

Abstract: Using comparable legal information, and empirical data from over 2000 members of the UK's University and College Union and 2000 staff in universities of the European states, gathered by means of similar surveys, this paper is a comparative assessment of the de jure protection for, and the de facto levels of, academic freedom enjoyed by academic staff in the UK, when compared to their EU counterparts. The paper examines the legal and constitutional protection for academic freedom and the current levels of, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Jungblut and colleagues (2020) argue that 'in some of the EHEA countries the adherence of fundamental values, e.g., with respect to academic freedom, has deteriorated instead of improved since 2010' (p. 185). One of the most recent studies on academic freedom in the UK reported the low protection of academic freedom, which has declined in recent years (Karran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jungblut and colleagues (2020) argue that 'in some of the EHEA countries the adherence of fundamental values, e.g., with respect to academic freedom, has deteriorated instead of improved since 2010' (p. 185). One of the most recent studies on academic freedom in the UK reported the low protection of academic freedom, which has declined in recent years (Karran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Jungblut and colleagues (2020) argue that ‘in some of the EHEA countries the adherence of fundamental values, e.g., with respect to academic freedom, has deteriorated instead of improved since 2010’ (p. 185). One of the most recent studies on academic freedom in the UK reported the low protection of academic freedom, which has declined in recent years (Karran et al., 2021). This echoes the 2020 report by V‐Dem scholars arguing that despite many self‐commitments by governments and universities, academic freedom is under attack in many places (Spannagel et al., 2020), indicating that the gap between the commitment and realisation of academic freedom principles is also evident beyond post‐Soviet systems.…”
Section: Discussionmentioning
confidence: 99%
“…While to many policymakers, performativity is an effective tool for bringing about change, holding teachers accountable and identifying high-performing educators, it is also commonly linked to the erosion of academic professional freedom for both students and academics (Ball, 2012). A comparative assessment of academic freedoms by Karran et al. (2022) revealed that two substantive elements (freedom to teach and freedom to research) and three supportive components (autonomy, governance and tenure) have declined within the UK and EU Member States, but are significantly greater in the UK within the neoliberal university of the twenty-first Century, and as a result, academic freedoms have markedly declined allowing such performative initiatives as the “Core Content Framework” to be implemented.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Vuonna 1997 Unesco määritteli akateemisen vapauden oikeudeksi, jota ei rajoiteta millään doktriinilla tai institutionaalisella sensuurilla ('IUPsyS -United Nations Activities ', 1998). Akateemista vapautta onkin kirjallisuudessa ansiokkaasti arvioitu yliopistojen autonomian perustuslaillisten, lainsäädännöllisten ja niiden omiin johtosääntöihin kirjattujen sääntöjen perusteella (Appiagyei-Atua et al, 2016;Karran et al, 2017;Karran & Mallinson, 2019). Esimerkiksi Suomessa tieteen, taiteen ja ylimmän opetuksen vapaus ja yliopistojen itsehallinto on turvattu perustuslaissa (16 § ja 123 §).…”
Section: Akateemisen Vapauden Käsiteunclassified
“…Akateeminen vapaus tukee opetuksen ja tutkimuksen laatua (Karran & Mallinson, 2019), mutta se on myös tärkeä arvo ja tavoite sinänsä. Vaarassa olevien tutkijoiden ja opettajien kohdalla akateeminen vapaus yhdistyy perustavanlaatuisiin ihmisoikeuksiin.…”
Section: Lopuksiunclassified